INSTABILITY OF CERTAIN NONLINEAR DIFFERENTIAL EQUATIONS OF FIFTH ORDER - Cemil Tunc; Muzaffer Ates (IndoMS, 2016)
This paper establishes certain sufficient conditions to guarantee the non-existence of periodic solutions for a class of nonlinear vector differential equations of fifth order. With this work, we extend and improve two related results in the literature from scalar cases to vectorial cases. An example is given to illustrate the theoretical analysis made in this paper.DOI : http://dx.doi.org/10.22342/jims.22.1.249.83-91